Inter-related transactions within a framework of transaction with the substantional property - Kozikov, Yuri E. (Journal of the Belarusian State University. Law, 2019)
The author considers a problem of qualification of transactions as inter-related within a framework of transaction with the substantial property. The current legislation concerning transactions with the substantial property criteria of the inter-related transactions of civil doctrine are considered and estimated. The article contains independently developed and proved by the author conclusions and offers focused on the improvement of the legislation concerning transaction with the substantial property and formation of uniform practice on the questions connected with definition, commission and contest of the inter-related transactions of company.
Keywords: transaction; transaction with the substantial property; inter-related transactions; procedure of transaction’s formation; challenging of the transaction with the substantial property